2019
DOI: 10.1109/access.2019.2904970
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Based RTD Fabricated via Additive Screen Printing Process for Flexible Electronics

Abstract: A novel nickel (Ni)-based resistance temperature detector (RTD) was successfully developed for temperature monitoring applications. The RTD was fabricated by depositing Ni ink on a flexible polyimide substrate using the screen printing process. Thermogravimetric analysis was performed to study the thermal behavior of the Ni ink, and it was observed that the Ni ink can withstand up to 200 • C before the decomposition of the binder in the ink system. Scanning electron microscopy and white light interferometry we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…This value indicates that the surface free energy of the substrate is higher than the surface tension of the prepared ink. Therefore, when evaluated in terms of printability, the prepared ink was compatible with the substrate [32].…”
Section: Resultsmentioning
confidence: 99%
“…This value indicates that the surface free energy of the substrate is higher than the surface tension of the prepared ink. Therefore, when evaluated in terms of printability, the prepared ink was compatible with the substrate [32].…”
Section: Resultsmentioning
confidence: 99%
“…Various temperature, strain, and pressure sensors have also been realized using additive screen-printing process. Turkani et al reported nickel (Ni)-based resistance temperature detector (RTD) on polyimide substrate for detecting wide range of temperatures varying from −60 • C to 180 • C (Figure 2j) [101]. The flexible RTD exhibited a relative resistance change of 113% with a temperature coefficient resistance (TCR) of 0.44%/ • C and response time of <10 s. The thin RTD film was also very stable and repeatable across the wide temperature ranges.…”
Section: Screen Printingmentioning
confidence: 99%
“…The usage of Cu is limited since it is prone to oxidation at low temperatures 59 . Ni, on the other hand, has the highest sensitivity and TCR relative to the other metals 36 .…”
mentioning
confidence: 98%
“…The rapid high heat generated during photonic curing is dissipated via thermal conduction at the interface of the substrate using the thermal mass of the substrate 22 . In the process, neck formation phenomena occur between metallic particles and cause grain growth of particles; then, pores are removed, and a dense continuous conductive layer is achieved [36][37][38][39] .…”
mentioning
confidence: 99%
See 1 more Smart Citation